If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(x + -1y) = 3x + -5 6 + (x * -2 + -1y * -2) = 3x + -5 6 + (-2x + 2y) = 3x + -5 Reorder the terms: 6 + -2x + 2y = -5 + 3x Solving 6 + -2x + 2y = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + -2x + -3x + 2y = -5 + 3x + -3x Combine like terms: -2x + -3x = -5x 6 + -5x + 2y = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -5x + 2y = -5 + 0 6 + -5x + 2y = -5 Add '-6' to each side of the equation. 6 + -5x + -6 + 2y = -5 + -6 Reorder the terms: 6 + -6 + -5x + 2y = -5 + -6 Combine like terms: 6 + -6 = 0 0 + -5x + 2y = -5 + -6 -5x + 2y = -5 + -6 Combine like terms: -5 + -6 = -11 -5x + 2y = -11 Add '-2y' to each side of the equation. -5x + 2y + -2y = -11 + -2y Combine like terms: 2y + -2y = 0 -5x + 0 = -11 + -2y -5x = -11 + -2y Divide each side by '-5'. x = 2.2 + 0.4y Simplifying x = 2.2 + 0.4y
| 64+7y=-13 | | a^2=4a+4 | | 10p-20=60 | | 8x^2-20x+9=0 | | 37+18+8w=67 | | 24+(-8)= | | z=0/3 | | 364=4t^2-53t+188 | | 4s+10=4-2 | | 1m+9=0 | | 55+25x=250+10x | | 9.25m+3.3=1.3-0.76 | | -7t=56 | | 200m-75m+57000=60300-175m | | 2-3k=-44 | | 10(x+4)=-(-8-9x)+3x | | -25w-7+9=-7 | | 7b+4=95 | | 3(x-3)=2(5) | | x(7x-1)+3=7x(x-3)x | | 2.1+y=10 | | w+2.7=8.9 | | 8=-0.0417t^2-.08333t+10 | | 2.1=p+(-9.3) | | X+x+2=77 | | 8m+20=8m+20 | | (x-3)1+6=(x-3)(x+3)1 | | 0.5=4.1x-(1.3x-4) | | n^2-12n-2=0 | | 72.1=p+(79.3) | | .7(x-2)=.7 | | lnx+lny^2=8 |